Symptomatic Hyponatremia in a Patient With Hepatorenal Syndrome Treated with Terlipressin. - Ahmed, Raheel; Ahmed, Tanveer; Munib, Syed (Pakistan Journal of Kidney Diseases, 2022)
Terlipressin (vasopressin analogue) is considered most promising pharmacotherapy used for reversal of hepatorenal syndrome and esophageal variceal bleed. It occasionally results in hyponatremia, often complicated by serious central nervous system manifestation. We report here a case of a 60 years’ old female known case of chronic liver disease decompensated who presented with acute kidney injury secondary to hepatorenal syndrome. Treatment was started with terlipressin loading dose followed by maintenance dose. She developed acute confusion, however there was no obvious brain pathology on computed tomography. Her baseline serum sodium (146.8mol/L) decreased to 111.5mmol/L after terlipressin was initiated. Terlipressin was withdrawn and responded to 3% hypertonic saline. Terlipressin-induced hyponatremia may be a rare complication and treating physicians should be aware of the possible complications arising during the management of hepatorenal syndrome.